Implementasi Pendidikan Karakter Melalui Pembelajaran Berbasis Proyek (Literature Review) - Jufri Jufri; Hasrijal Hasrijal (Departement of Mathematics Education, 2023)
Lately character education has become a worldwide trend. This arises due to the rapid development of the times, so it is feared that the character values in a society will disappear, especially the local character values in a society. This article explores research that has been conducted by several researchers regarding the implementation of character education through project-based learning. The method used is literature review, by collecting articles related to the research topic, then reviewed and then grouped based on the type of research. The results of the study show that not many studies have implemented character education through project-based learning.